Mental health status among intern doctors during COVID-19 pandemic in Bangladesh - Haque, Mohammad Mominul; Chowdhury, M. Tameem Shafayat; Islam, Sohana; Shafaatullah, A. A.; Zisan, F. M. Wasiul Islam; Rangan, Ibtihaz Kamal; Hawlader, Mohammad Delwer Hossain (International Journal of Research in Medical Sciences, 2026)
Background: The COVID-19 pandemic has imposed substantial physical and psychological burdens on healthcare workers worldwide, with high levels of anxiety, depression and stress reported among physicians, especially frontline staff. Intern doctors in Bangladesh, who work long hours in high-risk and resource-limited settings, may be particularly vulnerable; however, data on this group remain limited. This study aimed to assess the prevalence and determinants of depression, anxiety and stress among intern doctors in Bangladesh during the pandemic. Methods: This cross-sectional study included 317 intern doctors from public and private medical college hospitals, recruited through convenience sampling between April and July 2021. Data were collected using a structured questionnaire covering sociodemographic and work-related variables, along with the DASS-21 scale to measure depression, anxiety and stress. Statistical analysis was performed using SPSS, applying descriptive statistics, chi-square tests and binary logistic regression to identify factors independently associated with mental health outcomes, with p<0.05 considered significant. Results: A high prevalence of psychological distress was observed: 73.2% of participants had depression, 69.4% had anxiety and 51.1% had stress, with many experiencing severe or extremely severe symptoms. Working in private hospitals was independently associated with higher odds of depression (OR 2.25), anxiety (OR 3.81) and stress (OR 2.31). Experiencing occupational stigma and working overtime were also significant contributors. Conclusions: Intern doctors in Bangladesh experienced a substantial mental health burden during COVID-19. Targeted psychological support, improved workplace conditions and organizational interventions are urgently needed to safeguard their well-being.